Synergetic Effect of Nano-ZnO and Trinidad Lake Asphalt for Antiaging Properties of SBS-Modified Asphalt - Yiqun Zhan; Jun Xie; Yulin Wu; Yifan Wang (Advances in Civil Engineering)
In order to address the influence of aging on the performance degradation of SBS-modified asphalt, a composite modification of SBS-modified asphalt by nano-zinc oxide (nano-ZnO) and Trinidad Lake asphalt (TLA) was proposed. Several tests were conducted after adding nano-ZnO and TLA to SBS-modified asphalt, including a rotary film oven test (RTFOT), ultraviolet aging (UV), and the pressure aging vessel test (PAV). The conventional physical index, rheological index, and four-component content of SBS-modified asphalt before and after three aging modes were tested, and the characteristic functional groups in SBS-modified asphalt were tracked and analyzed by Fourier transform infrared spectroscopy (FTIR). The results show that the effects of aging on the rheological properties of SBS-modified asphalt are clearly reduced by adding different proportions of nano-ZnO and TLA in the process of thermal oxygen aging and the ultraviolet aging test, and the antiaging ability of SBS-modified asphalt is clearly improved. To improve the conventional performance and rheological properties of SBS-modified asphalt, an incorporation ratio of 3% nano-ZnO + 25% TLA was proposed. At the same time, the increased rate of heavy components and the change index of the colloidal instability index in the SBS-modified asphalt under the blending ratio were significantly lower than the blank SBS-modified asphalt samples in the same aging mode. FTIR spectra also showed that SBS-modified asphalt performance deterioration were mainly caused by long-term aging and ultraviolet aging. The addition of nano-ZnO and TLA effectively reduced the increase of carbonyl groups and the breakage of the C=C double bond in butadiene and synergistically improved the comprehensive aging resistance of SBS-modified asphalt. Therefore, the use of this modification is an effective method to solve the aging problem of SBS-modified asphalt.